2010
DOI: 10.1007/s12204-010-1019-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the liquid slug of cryogenic slug flow in inclined tubes

Abstract: An experimental study was carried out to understand the phenomena of the boiling flow of liquid nitrogen in inclined tubes with closed bottom by using a high speed motion analyzer. The experimental tubes are 0.018 and 0.014 m inner diameter (ID) and 1.0 m in length. The range of the inclination angle is 45 • -90 • from the horizontal. The experimental observation on the liquid slug was carried out along the tubes. Statistical method was employed to analyze the experimental data. The experiment analyzed the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
4
5
0
Order By: Relevance
“…This conclusion aligns with an empirical study, revealing that external motivators such as job prospects and income considerations are instrumental in Chinese female students' decision-making process when selecting an engineering education [35]. The perception of engineering as a conduit to diverse employment opportunities and lucrative financial returns has encouraged women to gravitate toward engineering fields in China [35]. However, personal ability and role models were not found to be critical factors influencing WPEE in this study.…”
Section: Key Factors For Promoting Wpee In Chinasupporting
confidence: 84%
See 2 more Smart Citations
“…This conclusion aligns with an empirical study, revealing that external motivators such as job prospects and income considerations are instrumental in Chinese female students' decision-making process when selecting an engineering education [35]. The perception of engineering as a conduit to diverse employment opportunities and lucrative financial returns has encouraged women to gravitate toward engineering fields in China [35]. However, personal ability and role models were not found to be critical factors influencing WPEE in this study.…”
Section: Key Factors For Promoting Wpee In Chinasupporting
confidence: 84%
“…Second, we found that employment expectations (X 12 ) also play a significant role in promoting WPEE in the Chinese cultural context. This conclusion aligns with an empirical study, revealing that external motivators such as job prospects and income considerations are instrumental in Chinese female students' decision-making process when selecting an engineering education [35]. The perception of engineering as a conduit to diverse employment opportunities and lucrative financial returns has encouraged women to gravitate toward engineering fields in China [35].…”
Section: Key Factors For Promoting Wpee In Chinasupporting
confidence: 82%
See 1 more Smart Citation
“…(4) Throttling groove The effect of a pressure drop on the valve body space and throttling loss should be considered when designing the throttle groove of the valve port. Here, the valve port pressure drop ∆p = 1.4 MPa was taken, and the maximum flow area A max of the throttle groove was preliminarily estimated to be about [26,27]…”
mentioning
confidence: 99%
“…The shape of the throttle valve port includes the milling groove type, semicircle moment type, semicircle type, cone type, triangular groove type, L-type, and multi-level throttling grooves composed of the aforementioned throttling grooves in series [26,27]. From the perspective of the linearization of flow regulation, V-shaped grooves were used.…”
mentioning
confidence: 99%